An Analysis of Structural Form of Identity Theft in Cyber - แก้วมี กิตติยา (NKRAFA Journal of Humanities and Social Sciences, 2020)
The objective of this study is to present identity theft in cyber which included structural forms, types of information, and the means to solve the problems of crimes. Nowadays the world becomes a place of information technology and borderless communication as the internet is connecting the world together, information technology, therefore plays a vital role in our daily life and becomes a part of our life. The internet can facilitate and respond to human needs to exchange the information between them which makes everyone trust in the system and expose their personal information to the public. Therefore, it is a loophole for criminals to access to the sensitive and confidential personal information including bank account information, credit information and taxation. These criminals would create fake accounts for their criminal purposes, for instance, driving license, passport, and etc. under the name of victims through the use of various tactics and modern technology as part of a tool to commit in crimes. This has a huge impact on the government, private sector, and the public because identity theft can be extended to various forms of crimes as it is easily accessible in all areas. Therefore, everyone and every sector need to raise an awareness to protect both oneself and their surrounding identity to narrow the loopholes and to avoid becoming a victim of such criminals. The most important thing is everyone must be aware and value their own identity and learn how to survive on the world of internet carefully and safely to protect oneself from becoming a victim and protect others to be safe and happy on the social networks and online communities.